1995
DOI: 10.1136/thx.50.9.972
|View full text |Cite
|
Sign up to set email alerts
|

Validation of British Thoracic Society guidelines for the diagnosis of the sleep apnoea/hypopnoea syndrome: can polysomnography be avoided?

Abstract: Background-The British Thoracic Society report on the diagnosis and treatment of the sleep apnoea/hypopnoea syndrome (SAHS) suggests that, ifthe pulse oximetry baseline oxygen saturation is above 90%,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(50 citation statements)
references
References 16 publications
3
43
0
3
Order By: Relevance
“…With an ODI cut-off at o15, three patients (17%) would have been missed by the MESAM-IV device and one patient (6%) would have been wrongly classified as being positive (sensitivity: 57%, specificity: 91%), which is in agreement with the findings of RYAN et al [9]. A low ODI threshold augments sensitivity at the expense of specificity.…”
Section: Comparison Studysupporting
confidence: 82%
See 1 more Smart Citation
“…With an ODI cut-off at o15, three patients (17%) would have been missed by the MESAM-IV device and one patient (6%) would have been wrongly classified as being positive (sensitivity: 57%, specificity: 91%), which is in agreement with the findings of RYAN et al [9]. A low ODI threshold augments sensitivity at the expense of specificity.…”
Section: Comparison Studysupporting
confidence: 82%
“…o15 desaturations of 4% per hour in bed. An apnoea-hypopnoea index (AHI) w15?h -1 , which was slept on PSG, was used as the objective measure of disease [9]. These authors found that the BTS criteria are highly specific when positive (100% specificity), but may miss sleep apnoeics with no significant desaturations (31% sensitivity).…”
mentioning
confidence: 98%
“…In the first place, not all studies are based on the same definition of AHI. For example, some previous studies conservatively employ values of AHI ≥ 15 events/hour (Ryan et al 1995, Lévy et al 1996, Lacassagne et al 1997, Sano et al 1998, Olson et al 1999, Magalang et al 2003, whereas others use AHI ≥ 5 events/hour to diagnose mild OSA (Chaudhary et al 1998, Littner 2000, Fernández et al 2004. We used a threshold of AHI ≥ 10 events/hour.…”
Section: Discussionmentioning
confidence: 99%
“…91 The use of home-based nocturnal oximetry alone as a screening tool for OSA has a sensitivity of only 31% and can lead to an underestimation of OSA severity. 92 Combinations of the above factors modestly raise the predictive abilities of various models to levels of 60 to 70%. More recent clinical prediction models that integrate specific clinical examination findings and/or home-based oximetry appear to have improved predictive capabilities and hold promise for risk stratification; however, further validation is required.…”
Section: Diagnosis Risk Stratification For Appropriate Referral For Pmentioning
confidence: 99%